The Effect of CSR Implementation on Company Performance Through Reputation: Case Study of Bukit Asam Tarahan - Annisa Azzahra Mahatma Ganie; Dorothy Rouly Haratua Pandjaitan; Nurul Husna (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to examine the relationship between Corporate Social Responsibility (CSR) and company reputation in state-owned enterprises (SOEs). The research analyzes how PT Bukit Asam Tbk Tarahan utilizes CSR as a strategy to enhance company performance, build its reputation, and strengthen customer trust. Primary data was collected from 39 middle and low-level management employees at PT Bukit Asam Tbk Tarahan, Bandar Lampung, using a Google Forms-based questionnaire measured on a Likert Scale. The analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method to test the direct and indirect effects between the independent variable (CSR), the dependent variable (Performance), and the intervening variable (Reputation). The results indicate that CSR has a positive and significant impact on reputation, which in turn positively affects company performance. However, CSR does not have a direct significant impact on company performance. Instead, CSR contributes positively to performance through the enhancement of the company's reputation. This suggests that CSR initiatives are more effective in improving the company’s standing in the community rather than directly boosting company performance. The study concludes that a strong reputation, bolstered by CSR, provides a competitive advantage and enhances stakeholder trust, ultimately contributing to improved company performance.